The Circular Economy Model of Kefir MSMEs: Combining Waste Valorization with Enterprise Sustainability - Cori Qamara; I Putu Gede Didik Widiarta; Amalina Nur Wahyuningtyas; Kirana Dara Dinanti Adiputra; Made Hardinata Wijakesuma (Universitas Airlangga, 2026)
Background: To combat environmental degradation and resource scarcity, a global shift from a linear to a circular economy is necessary. Kefir production offers significant potential for the circular economy by leveraging by-products such as whey and ricotta. Objective: This study describes the application of circular economy concepts within a kefir microenterprise in Samarinda, Indonesia, focusing on waste-recycling practices, profitability patterns, and sustainable business strategies. Method: A mixed-method approach combining digital ethnography, e-commerce data analysis, and indirect cost calculation was used to identify circular processes and their association with production costs. Results: Local producers have successfully transformed waste into functional foods and cosmetics. This study demonstrates that these producers naturally apply circular economy principles through practical experience. Converting by‑products into revenue streams helps offset the low profit margins of basic products, given the large gap between market prices and production costs. Conclusion: The growth and resilience of micro, small, and medium enterprises (MSMEs) in the kefir sector align with sustainability concepts. This article suggests strengthening value chain integration and encouraging greater collaboration among stakeholders to make the transition to a circular model more effective. Keywords: dairy product; fermented product; green economy; sustainability; waste valorization